THE USE OF SCRABBLE GAMES TO INCREASE STUDENTS’ VOCABULARY OF THE STUDENTS AT SMAN 4 BINJAI - Juliantina juliantina (Jurnal Serunai Bahasa Inggris, 2020)
The purposes of this study whether there is differentiate between students taught by using scramble games will be increasing students’ vocabulary or not. After collecting data by pre test, and post  test the result of data analysis showed that the first experimant gained t count = 3,21 >ttable = 2,39 with the significant was 5% and (t count = 3,21 >t table = 1,67) with the significant was 1%, and the second experiment showed that (t count = 3,52 >ttable =2,39) with the significant was 5% and (t count =3,52 >t table =1,67) with the significant was 1%. It meant that there was a significant increasing students’vocabulary at the eleventh grade of SMAN 4 Binjai. Based on the research above, the writer wants to take research at the second grade of Senior High School at SMAN 4 Binjai. The researcher focused his research in improving vocabulary ability through scrabble game.